Paraneoplastic retinopathy associated with occult bladder cancer - M Nivean; Danson V Muttuvelu; Pia Afzelius; Dalia C Berman (Indian Journal of Ophthalmology, 2016)
The aim was to report the first case of cancer-associated retinopathy (CAR) presenting before bladder cancer diagnosis. A 71-year-old woman with a history of bilateral vision loss underwent subsequent complete ophthalmic examination include a fluorescein angiography, full-field electroretinogram (ERG), serology including serum antibodies for CAR, and positron emission tomography-computed tomography (PET-CT) scan. The patient was diagnosed with bladder carcinoma revealed by PET-CT. Timely recognition of this entity may be crucial for an increased patient survival thus adult onset progressive photoreceptor dysfunction, confirmed by ERG, should alert to a possible remote effect of known or occult malignancy. In the latter, PET-CT may be exploited as a powerful diagnostic tool.